Covid-19 dalam Perjalanan Akhir Zaman: Sebab, Dampak dan Anjuran Syariat dalam Menghadapinya - Mukran H. Usman; Aswar, Aswar; Zulfiah Sam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Rasulullah saw. had informed muslims about the occurrences that will befall mankind on their way to the end of time, including the evil disasters that will hit the earth, kill, and destroy the human being. As a muslim, there is no word except that we believe in the occurrences and phases of the journey towards the end of the time. This study aimed to explain one of the occurrences of the journey towards the end of time that befall the world and mankind today, which is one of the deadly infectious outbreaks so-called coronavirus or covid-19, which has destroyed many people, imprisoned people in cities and countries, and caused various disasters and havocs as the result of the outbreak. The research method used was library research which was through a literature review related to the research. The results showed that the information of the journey towards the end of time would appear one by one in the range of human life, how they live, so thus Allah swt. shows them the meaning of the age they lived in. The worse human life is, the more Allah swt. show the badness of that era to the point where it is rampant engulfing the world and mankind, even though among those times are pious people, whether in an Islamic country or groups. Muslims are encouraged to follow the Shari'a when an epidemic strikes a country, namely: 1) not entering a country affected by disaster; 2) close the container where the water is; 3) pray a lot and recite; and 4) living in the city of Medina; stay indoors. Finally, the effects of the plague at the end of time are: 1) the number of sudden deaths; and 2) humans are isolated.